AB0268 Acpa seropositivity and peripheral natural killer cells as predictive markers of clinical response to rituximab in rheumatoid arthritis patients. (15th June 2017) - Ferreira, RM; Fonseca, R; Gonçalves, DR; Aguiar, F; Rocha, TM; Bernardo, A; Pimenta, S; Bernardes, M; Costa, L
Abstract : Background: The efficacy of B cell-depletion therapy confirms the importance of B lymphocytes in rheumatoid arthritis's (RA) pathogenesis. Rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA) are prognostic factors for a more severe disease. Others immune elements, namely natural killer (NK) cells, seems to influence RA clinical response to rituximab (RTX), but data are lacking. Objectives: To analyze the influence of baseline status/levels of RF, ACPA and serum immunoglobulin G (IgG) level in RTX treatment. To study the effect of RTX on NK and CD19+ cells in RA patients and their association with clinical response at 6, 12 and 18 months (M). Methods: An observational retrospective study was conducted, including all the consecutive patients with diagnosis of RA under rituximab, followed at our Rheumatology department. Demographic and clinical data were obtained by consulting the national database (Reuma.pt) and the analysis was limited until december 2016. RF, ACPA and IgG titres were evaluated at baseline. NK (CD56+CD16+) and B lymphocytes (CD19+) absolute counts were assessed by flow cytometry prior to the first RTX cycle and 6 M after. Clinical responses were assessed by DAS28 and EULAR criteria at 6, 12 and 18 M. Correlations were studied using Spearman coefficient analysis (SPSS 20.0). Significance level was set as 0.05. Results: We included 63 RA patients (81% of women), with a mean (SD) age of 61 (10) years and a mean disease duration of 19 (10) years, 86% RF-positive and 87% ACPA-positive. Bone erosions were present in 86% of the patients. At baseline, the mean DAS28 was 5.79 (1.55). Combination therapy with methotrexate or with others cDMARDs was used in 48% and 30% of the patients, respectively; RTX monotherapy in 22% of our sample. Thirty three patients were previously exposed to other biologics. The magnitude of response was greater in ACPA-positive vs ACPA-negative patients in terms of DAS28 variation at 6, 12 and 18M (medians of 1.09 vs -0.08; 2.03 vs 0.35 and 2.10 vs 0.19; p=0.029, p=0.039 and p=0.004, respectively), without significant differences between groups in terms of initial DAS28 (5.91 (1.60) vs 5.00 (0.90), p=0.051). The presence of ACPA was also significantly associated with EULAR response at 6, 12 and 18 M (64%, 75% and 85% in ACPA-positive patients vs 25%, 16% and 25% in ACPA-negative patients; p=0.034, p=0.010 and p=0.001, respectively). Outcomes did not differ according FR status. There were no associations between the values of FR, ACPA and IgG at baseline with the clinical response (DAS28 variation). CD19+ cells depletion occurred in all patients (mean of 146.4/mm 3 at baseline vs 10.6/mm 3 at 6M). An increase of peripheral NK cells was seen at 6M (mean 231mm/3 at baseline vs 289/mm 3 at 6 M). We only have found a positive correlation between NK cells number at baseline and DAS28 variation at 6 M (r=0.35, p=0.023). There were no associations between, neither NK cells, nor CD19 cells variations at 6M with clinical response to RTX. Conclusions: Our data suggest that ACPA seropositivity is associated with a better clinical response to RTX in RA patients. NK cells at baseline may be useful to identify early responders to RTX. Disclosure of Interest: None declared